2016
DOI: 10.1148/radiol.2015150959
|View full text |Cite
|
Sign up to set email alerts
|

18F FDG PET/CT versus CT/MR Imaging and the Prognostic Value of Contralateral Neck Metastases in Patients with Head and Neck Squamous Cell Carcinoma

Abstract: CNM from HNSCC can be detected at FDG PET/CT with higher sensitivity and accuracy than at CT/MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…Our findings suggest that PET/CT is more sensitive than CECT in detecting the presence of cervical lymph node metastases only when ruling out disease to a given neck side, which is in accordance with previous studies. 5,1119 In particular, PET/CT was 28% more sensitive than CECT in detecting neck sides that contained metastatic lymphadenopathy ( p =0.001). 50 of 53 (94%) positive neck sides were correctly identified by PET/CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that PET/CT is more sensitive than CECT in detecting the presence of cervical lymph node metastases only when ruling out disease to a given neck side, which is in accordance with previous studies. 5,1119 In particular, PET/CT was 28% more sensitive than CECT in detecting neck sides that contained metastatic lymphadenopathy ( p =0.001). 50 of 53 (94%) positive neck sides were correctly identified by PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…10 Others propose the newer fluorodeoxyglucose (FDG) positron emission tomography (PET) combined with low-dose noncontrast computed tomography (PET/CT) as the more accurate modality. 5,[11][12][13][14][15][16][17][18][19] However, using PET/CT alone for preoperative planning can be problematic due to limited resolution and high false-positive rates. 20 Thus, our objectives were (1) to assess and compare the accuracy of PET/CT and CECT in detecting cervical nodal metastases and (2) to scrutinize the ability of each modality and the combination of these modalities to accurately determine nodal stage.…”
mentioning
confidence: 99%
“…It is interesting to note that all patients in the current series underwent surgical resection of the tonsil primary tumor, and the majority of patients underwent unilateral neck dissection and staging FDG‐PET. These 3 factors allowed for pathological staging of the primary tumor and ipsilateral neck disease, as well as potentially reducing the risk of occult contralateral disease …”
Section: Discussionmentioning
confidence: 99%
“…These 3 factors allowed for pathological staging of the primary tumor and ipsilateral neck disease, as well as potentially reducing the risk of occult contralateral disease. 25 To the best of our knowledge, the only prospective study regarding unilateral neck RT in patients with tonsillar cancer published to date was by Rusthoven et al, who delivered unilateral RT to 14 of 20 patients with tonsillar cancer with N1 to N2b disease and observed no in-field or contralateral recurrences. 26 The majority of patients had T1 to T2 (18 of 20 patients) and N2b (13 of 20 patients) disease and unilateral treatment was only given for tumors without involvement of the base of the tongue or soft palate.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of metabolic activity from PET/CT has already been reported to be very helpful in the evaluation of treatment response [34]. Prior studies in patients with HNSCC have shown that 18 F FDG PET/CT has a higher diagnostic accuracy compared to MRI for assessment of untreated HNSCC [35] or treated HNSCC [36]. However, these studies did not include MRI with DWI, which obviously influences the diagnostic performance.…”
Section: Tablementioning
confidence: 99%